P174 Severity of Bronchiectasis on High Resolution CT Scanning and Its Relationship to Chronic Bacterial Colonisation. (19th November 2012) - Stretton, RJ; Leighton, KE; Marshall, S; Schembri, S; Fardon, T; Chalmers, JD
Abstract : Introduction: Bacterial colonisation and particularly colonisation with Pseudomonas aeruginosa is associated with a more severe clinical course in bronchiectasis. It is often presumed that patients with more extensive radiological bronchiectasis are at higher risk of chronic bacterial colonisation, but data on this is lacking. The aim of this study was to determine if severity of bronchiectasis on HRCT predicts chronic bacterial colonisation. Methods: Data was collected from a specialist bronchiectasis clinic from April 2011 to April 2012. A total of 88 patients were diagnosed with bronchiectasis following assessment by a respiratory physician and a high resolution CT scan. Sputum cultures from the previous 2 years were used to determine colonisation status. The severity of disease on CT scanning was determined for each patient using a modified Reiff scoring system. This attributed to every lobe a score dependant on the type of Bronchiectasis seen and the number of lobes involved – Cylindrical=1, Varicose=2, Cystic=3. The minimum score is 1 and the maximum score is 18. Results: 88 patients had bronchiectasis confirmed on HRCT by a clinical radiologist. For each set of patients colonised with a particular organism the average Reiff score was calculated. 11 patients had P. aeruginosa (Reiff mean 5.6, SD 4.8). This score was significantly higher than those patients colonised with other pathogenic microorganisms (Reiff mean 3.4, SD 2.9) (p=0.03), and for patients not colonised with microorganisms (Reiff mean 3.0, SD 2.2) (p=0.005).- figure 1 . Among the other organisms isolated 29 patients had Haemophilus influenzae (Reiff Mean 3.7, SD 3.5). This mean Reiff score was significantly lower than for P. aeruginosa, (p=0.03) – figure 1 . Streptococcus pneumoniae (Reiff Mean 3.4), Moraxella catarrhalis (Reiff Mean 3.7) and Staphylococcus aureus (Reiff Mean 3.2), were also isolated in lesser numbers and a further 28 patients had a mix of other colonising organisms (Reiff Mean 3.5). Conclusion: More severe radiological bronchiectasis is associated with the presence of bacterial colonisation and particularly colonisation with Pseudomonas aeruginosa . This simple assessment of radiological severity may be a useful clinical tool in non-CF bronchiectasis.